MENYULAM NUSANTARA: EKSPLORASI ALAT MUSIK RINDING/KNOBE OH KABUPATEN TTS PADA PEMBELAJARAN BAHASA INDONESIA - Tefa, Maria Dolorosa Fransiska; Batti, Margaritha; Nay, Florianus Aloysius (Universitas Borneo Tarakan, 2025)
Traditional musical instruments are an integral part of Indonesia's rich and diverse culture. One particularly fascinating instrument is the Rinding/Knobe, which originates from South Central Timor Regency (TTS), East Nusa Tenggara. This musical instrument not only holds artistic value but also represents the cultural identity of the local community. This study aims to explore the potential of the traditional musical instrument Rinding/Knobe Oh in Indonesian language learning within the Merdeka Curriculum. Using a qualitative approach, this research analyzes data from interviews, observations, and documentation to understand how this instrument can integrate local cultural values into the learning process. The findings indicate that introducing the Rinding/Knobe Oh musical instrument can enhance students' interest and motivation, enrich their learning experience, and contribute to the preservation of local culture. This culture-based learning approach not only helps students grasp language concepts but also fosters a sense of appreciation for the nation's cultural heritage. The implications of this study highlight the importance of integrating local arts and culture into the curriculum to create a more meaningful and relevant learning experience for students.